CO43 | Early platelet dysfunction in sepsis: an ICU pilot study (Bleeding, Thrombosis and Vascular Biology)
Background and Aim: Platelets play a key role in hemostasis and immune response during infection. In sepsis, platelets interact with endothelial cells and leukocytes, contributing to inflammation and microvascular thrombosis. Thrombocytopenia is a known marker of poor prognosis, whereas platelet dysfunction during sepsis has barely been investigated. This study aims at exploring early platelet function changes in septic patients and their corrrelation to sepsis severity markers, such as procalcitonin and SOFA score. Methods: Ten adult patients with sepsis or septic shock admitted to the ICU of «Fondazione Policlinico Universitario A. Gemelli» and seven healthy controls were enrolled. Blood samples were collected at admission (T0), after 48 hours (T1) and 7 days (T2). We performed the following tests 1) light transmission aggregometry (LTA) on samples with platelet counts ≥150×10³/μL2) flow cytometry measurement of platelet P-selectin and PAC-1 expression 3) flow cytometry measurement of platelet–leukocyte aggregates; 4) thromboelastography (TEG) platelet mapping to measure maximal platelet aggregation induced by ADP and arachidonic acid in whole blood 5) ELISA measurement of plasma soluble P-selectin and CD40L levels. Platelet activation markers were correlated with procalcitonin levels and SOFA scores. Healthy controls were sampled only at T0.